034 The susceptibility vessel sign: a clinical-radiological case of propagating left MCA thrombus with resolving neurological deficits. Issue 6 (24th May 2018) - Nham, Benjamin; Hawke, Simon
Abstract : Introduction: The susceptibility vessel sign (SVS) is a radiological sign on the SWI sequence of MRI that can predict cardioembolic source and increased recanalisation rates in stroke. 1 We present a case of an 86 year old female with resolving neurological deficits from a propagating left MCA thrombus with positive SVS on imaging. Case: An 86 year old female presented with sudden onset right sided weakness and expressive aphasia in the context of new atrial fibrillation. Her NIHSS was 4. Initial CT angiogram showed complete occlusion of the proximal M1 segment of the left middle cerebral artery. She was within the thrombolysis window but her deficits largely resolved (NHISS 0) before thrombolysis could be administered. A repeat CT angiogram one hour after the first scan showed complete resolution of the MCA occlusion. An MRI brain showed curvilinear gradient signal hypointensity in the distal left M2 segment of the MCA (positive SVS) with a small area of infarction and restricted diffusion. She was discharged on apixaban without neurological deficit. This is a unique case of a stroke patient, with proximal large vessel occlusion, presenting with neurological deficits that self-resolved within minutes without thrombolysis or thrombectomy. There was a positive SVS on MRI. This radiological sign allows direct visualisation of the hypointense thrombo-embolus on the SWI sequence. It occurs as there is a higher level of deoxy-haemoglobin content in the thrombo-embolus and is predictive of a cardioembolic source as cardioembolic thrombi are rich in erythrocytes 1 . Conclusion: Our case demonstrated interesting clinical-radiological-pathological correlation in cardioembolic stroke with resolving neurological deficits. The patient's clinical improvement matched the radiological improvement and corresponded to the pathophysiological course of thrombus from embolization, propagation, occlusion, dissolution and then recanalisation. The SVS is a useful radiological sign to predict cardioembolic sources of stroke and is associated with higher vessel re-canalisation rates. Reference: . Cho KH, Kim JS, Kwon SU, et al. Significance of susceptibility vessel sign on T2*-weighted gradient echo imaging for identification of stroke subtypes. Stroke2005;36:2379–2383.